Reimajinasi Sistem Pembuktian: Apakah Era Post-Faktual Membutuhkan Standar Baru dalam Hukum Acara Pidana? - Zul Khaidir Kadir (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The post-factual era has shifted the position of legal facts from objective entities to part of narrative contestations shaped by digital disinformation, algorithmic media, and unverified public perception. Unfortunately, this has given rise to epistemic dislocation in the judicial process, where evidence loses its objective quality, legal decisions are distorted by collective emotional pressure and erode the credibility of the law as a guarantor of substantive and procedural justice. This research is a normative research using a conceptual approach. The data collection method was collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study show that the development of disinformation, emotional narratives, and manipulative digital evidence have shown a structural inconsistency between conventional evidentiary standards and the complexity of 21st-century legal realities, threatening the validity of evidence, the autonomy of judicial institutions, and the principle of due process in the criminal system. Therefore, it is necessary to reconstruct the evidentiary system through the integration of verification technology, cross-disciplinary collaborative approaches, and investment in digital literacy, to ensure that the law continues to function as a rational and fair instrument in an increasingly unstable information landscape.